The Effectiveness of TBMs in Promoting a Culture of Literacy in the Digital Age - Afina Zatil Isnan Maruhawa; Eniya Rianta Sema Kudadiri; Putri Elpatisia Siringo; Joharis Joharis (International Journal of Educational Evaluation and Policy Analysis, 2025)
Academic literacy is one of the main factors in improving the quality of college graduates. Developed countries have implemented various strategies to improve literacy levels in higher education environments in order to create competitive graduates who are ready to face global challenges. This article aims to analyze policies and implementation of strategies to improve academic literacy in universities in developed countries. Using a qualitative approach based on literature studies, this study found that technology integration, research-based learning, improving criteria, and providing supporting facilities such as digital libraries and academic literacy training are effective steps in improving student literacy. The results of this study are expected to be a reference for higher education institutions in developing countries in designing policies to improve academic literacy